Discovery of Cyanobacteria Associated with Cycads and Description of Three Novel Species in Desmonostoc (Nostocaceae) - Melissa H. Pecundo; Tao Chen; Thomas Edison E. dela Cruz; M. Patrick Griffith; Zhangli Hu; Huirong Chen; Nan Li (Diversity, 2023)
Heterocyte-forming cyanobacteria form symbiotic relationships with several lineages of plants. Here, twenty (20) strains of endosymbiotic cyanobacteria (cyanobionts) with Nostoc-like morphologies were isolated from the highly specialized coralloid roots of five host species in Cycadales—Cycas debaoensis, C. fairylakea, C. elongata, Ceratozamia robusta, and Macrozamia moorei. Molecular phylogeny based on the 16S rRNA gene placed these strains into seven different taxa within the Nostocaceae, specifically under the genera Desmonostoc and Dendronalium. The percent dissimilarity and unique patterns in the secondary structures of the D1-D1′, Box-B, V2, and V3 helices, which were based on the 16S–23S rRNA internal transcribed spacer (ITS) regions, supported three distinct species in Desmonostoc. These three morphologically distinct novel species are described in this report: Desmonostoc debaoense sp. nov., Desmonostoc meilinense sp. nov., and Desmonostoc xianhuense sp. nov. Other investigated strains were phylogenetically identified as members of the recently discovered genus Dendronalium and represent the first report of association of that genus with cycads. Our findings suggest that the order Cycadales hosts diverse species of cyanobionts in their coralloid roots and that many potential unreported or novel taxa are present in cycads occurring in their natural habitat and await discovery.